Multiscaling analysis of high resolution space-time lidar-rainfall - Lewandowski, P. (2012)
In this study, we report results from scaling analysis of 2.5 m spatial and 1 s temporal resolution lidar-rainfall data. The high resolution spatial and temporal data from the same observing system allows us to investigate the variability of rainfall at very small scales ranging from few meters to ~1 km in space and few seconds to ~30 min in time. The results suggest multiscaling behaviour in the lidar-rainfall with the scaling regime extending down to the resolution of the data. The results also indicate the existence of a space-time transformation of the form t~Lz at very small scales, where t is the time lag, L is the spatial averaging scale and z is the dynamic scaling exponent.